Nonlinear optical borate crystals : principles and applications - Chen, Chuangtian, 1937- (Weinheim : Wiley-VCH, 2012)
This clear and self-contained review of the last four decades of research highlights in the hot field of nonlinear optical (NLO) crystals, particularly of borate-based ultraviolet and deep-ultraviolet NLO crystals, covers three major subjects: the structure-property relationship in borate crystals, the structural and optical characteristics of various promising borate crystals, and their fruitful applications in a wide range of scientific and technological fields.
Theoretical Basis for the Development of Borate Nonlinear Optical Crystals -- Borate Nonlinear Optical Crystals for Frequency Conversion -- Other Borate Crystals -- Applications.
Includes bibliographical references and index.
Print version record.
Keywords: Crystal optics; Borate crystals -- Optical properties; Nonlinear optics; SCIENCE -- Physics -- Crystallography; Electronic books; Electronic books